Development of Bio-FET sensor for the detection of Boron - Bhattacharya, Sayantani (TIET, Patiala, 2019)
Boron is an essential micronutrient for the plants and plays a major role in development of animals and human. The rise in industry of glass, ceramic, cosmetic, soaps, and detergent caused emission of larger amount of boron into the atmosphere, soil, and water. On exposure to this excess boron, the living beings are suffering from serious health hazards and this is also causing death of the plants. Several methods have been implemented to determine their concentration such as spectrophotometric methods, but these methods suffer as they’re not very sensitive and precise, require large sample volume, sophisticated instrument, and are expensive. This lead to develop a sensor that will overcome the drawbacks of earlier method of boron determination. Bio-FET sensor was then designed on SILVACO TCAD tool based on the doping concentration of boric acid into different biopolymers to check for small change in dielectric and large change in threshold voltage of the sample solution.
MSc Biotechnology Thesis
Keywords: Bio-FET; Capacitance; Dielectric Constant; JL-MOSFET; Threshold Voltage